Therapeutic benefits of enhancing permeability barrier for atopic eczema - George Man; Peter M. Elias; Mao-Qiang Man (Wolters Kluwer Medknow Publications, 2015)
The regulatory role of epidermal permeability barrier function in cutaneous inflammation has been well appreciated. While barrier disruption induces cutaneous inflammation, improvement of permeability barrier function alleviates inflammation. Studies have demonstrated that improvement of epidermal permeability barrier function not only prevents the development of atopic eczema, but also delays the relapse of these diseases. Moreover, enhancing the epidermal permeability barrier also alleviates atopic eczema. Furthermore, co-applications of barrier enhancing products with glucocorticoids can increase the therapeutic efficacy and reduce the adverse effects of glucocorticoids in the treatment of atopic eczema. Therefore, utilization of permeability barrier enhancing products alone or in combination with glucocorticoids could be a valuable approach in the treatment of atopic eczema. In this review, we discuss the benefits of improving the epidermal permeability barrier in the management of atopic eczema.